2012
DOI: 10.1177/1555343412459192
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Relative Cue Strength as a Means of Validating an Inventory of Expert Offender Profiling Cues

Abstract: Cues have been identified as important precursors to successful diagnoses among expert practitioners. However, current approaches to the identification of expert cues typically rely on subjective methods, making the validity of cues difficult to establish. The present research examined the utility of a Paired-Concept Association Task (P-CAT) as a basis for discriminating expert and novice cue activation in the context of offender profiling. Three studies are reported: 1A employed a cognitive interview for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…Examples include the related terms ‘heavy traffic’ (feature) and ‘short-cut’ (event) and relatively less related terms ‘traffic-light’ (feature) with ‘free-way’ (object). Higher levels of cue utilization are associated with a greater variance in the perceived relatedness of terms ( Ackerman and Rathburn, 1984 ; Schvaneveldt et al, 2001 ; Morrison et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the related terms ‘heavy traffic’ (feature) and ‘short-cut’ (event) and relatively less related terms ‘traffic-light’ (feature) with ‘free-way’ (object). Higher levels of cue utilization are associated with a greater variance in the perceived relatedness of terms ( Ackerman and Rathburn, 1984 ; Schvaneveldt et al, 2001 ; Morrison et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, one proposition could be the development of hybrid virtual patients, which combine simulation with real-word cue representations (e.g., extracting patient responses from clinic assessment and treatment recordings); however, the obvious limitations relating to the sensitive nature of the current context must be weighed. Further, the method for initial cue-elicitation (i.e., CTA/CDM) could be enhanced by using it in combination with other more objective and/or on-line methods (e.g., eye-tracking), including those that gauge relative cue strength (e.g., Paired-Concept Association Task: Morrison, Wiggins, Bond & Tyler, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cues in decision-making has been demonstrated across numerous domains, including firefighting (Klein, Calderwood, & Clinton-Cirocco, 1986), medical diagnoses (Hammond, Frederick, Robillard, & Victor, 1989), courtroom judgments (Ebbesen & Konecni, 1975), aviation (Stokes, Kemper, & Marsh, 1992), driving (Fisher & Pollatsek, 2007), nursing (Shanteau, 1991), and crime-scene investigation (Morrison, Wiggins, Bond, & Tyler, 2013). Furthermore, differences in cue-use have been shown to, in part, differentiate differences in performance (Wickens & Hollands, 2000) It is proposed here that the extraction of knowledge from experienced clinical practitioners, in the form of criticalcues engaged during psychological assessment, may present a promising avenue in the development of more ecologically valid simulations of practitioner-patient interaction.…”
Section: Introductionmentioning
confidence: 98%
“…& Carr. 2002;: Loveday, Wiggins, & Searle, 2013Morrison, et al, 2013;Schriver et al, 2008 ;Perry, Wiggins, Childs, & Fogarty, 2013). As a result, cue use is viewed as a prominent avenue of interest for NDM researchers looking to model proficient processes in training programmes.…”
Section: Naturalistic Decision-making (Ndm) Paradigmmentioning
confidence: 99%
“…This suggested that players do not just use cues in isolation, but rather, it is the association between each of the cues which activates the conditioned-action response. Morrison, et al (2013) suggested that cues which are correlated together form cognitive links. These links result in a reduction in amount of cognitive resources used rather than if the individual had to consider the cues separately.…”
Section: Cue Use and Rugby Leaguementioning
confidence: 99%